Efisiensi Produksi Keripik Bakso melalui Implementasi Teknologi di Kelurahan Potrobangsan Magelang - Mulyaningsih, Nani; Safitra, Mohamad Nanda; Khusna, Kunti Nafingatul; Hastuti, Sri; Iftitah, Siti Nurul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Meatball chips craftsmen in Potrobangsan Village Magelang are home-based craftsmen who produce various types of meatball chips. The problem is that the meatball chips produced are easily soggy and less durable. This is because the craftsmen still use manual tools in the oil draining process because the efficiency of the production process decreases. The purpose of this service activity is to help partners to increase their production efficiency through the implementation of technology hope it's a solution partner problems. The technology in question is an oil draining machine. This program is implemented using socialization and training methods and demonstration of operation and maintenance of tools so that partners can improve product quality. The results of the service showed that with the implementation of technology, production efficiency increased because the time used became faster.